Brand Equity, Brand Experience, Consumer Satisfaction and Loyalty [THESIS] / Ridhwan Olatunji Olaoke Submitted to - Olaoke, Ridhwan Olatunji (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This study was aimed at evaluating whether brand experience mediates the effects of the components of Consumer Based Brand Equity (CBBE) i.e. lifestyle congruence, staff behavior, physical quality and self-congruence and on consumer satisfaction and loyalty within the confines of Famagusta, North Cyprus. The research adopted a quantitative research methodology where a number of surveys were distributed within Eastern Mediterranean University with a remarkable response rate. An analysis was conducted that proved that most of the respondents had a clear understanding of the survey. Analysis was done using the structural equations modelling test following the bootstrapping method. However necessary reliability and validity tests were carried out for the scales likewise the confirmatory factor analysis for the construct. The results of the study showed that brand experience did not mediate the effects of the dimensions of CBBE on brand loyalty. However, brand experience did fully mediate the effects of two of the dimensions of CBBE i.e. brand identification and lifestyle congruence which signifies that consumers tend to be more satisfied with brands that give experiences that match with their lifestyles and self-concepts. The research also further confirmed the facts from previous research that CBBE does have an effect on consumer satisfaction and loyalty. The study recommended that managers and marketers should seek to understand the interests and needs of consumers and give them experiences that would match their self-concepts and lifestyles thereby stimulating them to show attachment to the brand and identify with it.

ÖZ: Bu çalışmanın amacı marka tecrübesinin “Müşteri Tabanlı Marka Değer” bileşenlerini hangi yönde etkilediğini değerlendirmek ve araştırmaktır. Ayrıca, Müşteri Tabanlı Marka Değer faktörünü oluşturan “yaşam tarzı uyumu”, “çalışan davranışı”, “fiziki kalite”, “uyum” bileşenlerinin Gazimağusa’daki tüketicilerin davranışları üzerine etkisini değerlendirmektir. Araştırmamızda kantitatif araştırma yöntemi kullanılmış ve literatür taraması sonucunda oluşturulan anket Doğu Akdeniz Üniversitesinde dağıtılarak veriler elde edilmiştir. Anketin çoğu katılımcılarımız yönünden temiz bir anlaşılabilirliği olduğunu gösteren çalışma da ayrıca yapılmıştır. Yapısal Eşitlik Modellemesi istatistiksel yöntem kullanılarak ortaya konan kavramsal model bootstrapping yöntemi ile test edilmiş ve bulgulara ulaşılmıştır. Bunun yanında, modelde kullanılan değişkenlerin güvenilirliği Cronbach alfa ve doğrulama faktör analiz yöntemleri ile analiz edilmiştir. Araştırma sonunda elde edilen bulgular marka tecrübesinin Müşteri Tabanlı Marka Değer bileşenlerini etkilemediği bulgusunu ortaya çıkarmıştır. Bunun yanında, marka tecrübesi boyutunun “Müşteri Tabanlı Marka Değer” bileşenlerinden iki tanesinin markada sadakatini tam olarak etkilediği sonucuna da varılmıştır. Çalışma sonucunda pazarlamadan sorumlu yöneticilerin müşteri ilgi ve ihtiyaçlarını daha iyi anlamaları için araştırma yapmaları müşterilerin benlik kavramı ve yaşam tarzlarını uyumlaştırmaları gerektiği anlaşılmıştır.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Brand loyalty--Brand choice; Consumer-Based Brand Equity; Brand Identification; Brand Experience; Brand Loyalty; Consumer Satisfaction